Practice teaching a reflective approach - Richards, Jack C. 1943- (Cambridge University Press, 2011)
Written for language teachers in training, this book surveys issues and procedures in conducting practice teaching. Written for language teachers in training at the diploma, undergraduate, or graduate level, Practice Teaching, A Reflective Approach surveys issues and procedures in conducting practice teaching. The book adopts a reflective approach to practice teaching and shows student teachers how to explore and reflect on the nature of language teaching and their own approaches to teaching through their experience of practice teaching